2022
DOI: 10.1186/s13102-022-00505-2
|View full text |Cite
|
Sign up to set email alerts
|

What are the odds? Identifying factors related to competitive success in powerlifting

Abstract: Background The ability for athletes to gain a competitive advantage over their opponents is well recognised. At times, this advantage may be considered a marginal gain. However, in the context of competition, marginal advantages may be the difference between winning and losing. This investigation explores how competition factors influence the odds of competitive success (i.e. winning) in powerlifting (PL) to assist athletes and coaches in achieving a competitive advantage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…Here, upper-arm girth when the muscles were tensed was used as a surrogate for assessing the muscle cross-sectional area. Although we cannot confirm our theory regarding differences in body composition and lean body mass of GM athletes compared with SBM athletes, similar research conducted by van den Hoek et al (16) made similar conclusions for able-bodied PL athletes competing in the IPF. A secondary hypothesis to explain strength differences in the absence of difference in body mass and without data to support differences in body composition is that high-performing athletes are more experienced in competition and have improved kinematic strategies and movement-specific skill.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Here, upper-arm girth when the muscles were tensed was used as a surrogate for assessing the muscle cross-sectional area. Although we cannot confirm our theory regarding differences in body composition and lean body mass of GM athletes compared with SBM athletes, similar research conducted by van den Hoek et al (16) made similar conclusions for able-bodied PL athletes competing in the IPF. A secondary hypothesis to explain strength differences in the absence of difference in body mass and without data to support differences in body composition is that high-performing athletes are more experienced in competition and have improved kinematic strategies and movement-specific skill.…”
Section: Discussioncontrasting
confidence: 61%
“…Therefore, athletes aiming to improve from NPOD to POD positions with their final attempt may risk the increased likelihood of a failed attempt in exchange for a potential improvement in overall competition placing if the attempt is successful. Although not investigated in the current sample, van den Hoek et al (16) found that competition winners tended to have more experience competing than nonwinners within traditional PL likely resulting in a more refined competition day strategy. Coaches must also consider that competitive anxiety and other factors (sleep, tapering, etc.)…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Among the most practiced strength activities, gym activities and powerlifting stand out, both in conventional and Paralympic modalities (Aidar, Clemente, de Lima, et al, 2021;Fonseca et al, 2020;D. van den Hoek et al, 2023;D. J. van den Hoek et al, 2022).…”
Section: Introductionmentioning
confidence: 99%